Complications in cutaneous laser surgery - Goldberg, David J., M.D.; David J. Goldberg (London ; New York : Taylor & Francis, 2004)
laser have been successfully employed in clinical practice for the treatment of various disorders.
laser complications -- laser treatment in tattoos and pigmented laser treatment of unwanted hair and vascular lesions.
laser. includes index.
Includes bibliographical references and index.
All age.
Keywords: Skin -- Laser surgery -- Complications; Laser Surgery -- adverse effects; Skin -- surgery; Postoperative Complications -- diagnosis; Skin Diseases -- etiology